2001
DOI: 10.1002/jbm.1220
|View full text |Cite
|
Sign up to set email alerts
|

Protein adsorption and human osteoblast‐like cell attachment and growth on alkylthiol on gold self‐assembled monolayers

Abstract: Protein adsorption and growth of primary human osteoblasts on self-assembled monolayers of alkylthiols on gold (SAMs) with carboxylic acid and hydroxyl and methyl termini were investigated. Single-component SAMs and SAMs patterned by photolithographic techniques were used. Cell growth on patterned SAMs demonstrated preferences for one pattern region in all combinations of alkylthiols, with the hierarchical preference COOH > OH > CH(3). Patterned SAMs and immunochemistry were used to investigate adsorption of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 36 publications
9
131
0
2
Order By: Relevance
“…Surface wettability can be altered in many ways such as plasma treatment, surface coating, introduction of hydrophilic or hydrophobic groups by self-assembled monolayers (SAMs) 11,12,14,[22][23][24][25][26] . Among these methods, plasma treatment (radio frequency glow discharge) has a long history of modifying surface wettability.…”
Section: Discussionmentioning
confidence: 99%
“…Surface wettability can be altered in many ways such as plasma treatment, surface coating, introduction of hydrophilic or hydrophobic groups by self-assembled monolayers (SAMs) 11,12,14,[22][23][24][25][26] . Among these methods, plasma treatment (radio frequency glow discharge) has a long history of modifying surface wettability.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular selfassembly allows for the deposition of a self-assembled monolayer onto a substrate and subsequent exposure of an active terminal group that promotes specific biological functions such as the adhesion of protein and cells [94] or bone deposition [95]. This technique sounds promising because it allows obtaining a selective adhesion to the surface.…”
Section: Self-assembly Of Monolayers (Sams)mentioning
confidence: 99%
“…The adsorption of fibrinogen and platelet adhesion, for example, is inversely related to the hydrophilicity of the surface [94,131]. In a study, the authors found that cells were unable to adhere to hydrophobic surfaces previously coated with albumin but could easily adhere to hydrophilic surfaces covered with albumin [132].…”
Section: Protein/surfacementioning
confidence: 99%
“…Indeed, PEA based copolymers containing hydroxyl groups have already proven to trigger the formation of fibronectin networks on their surfaces, provided that the fraction of the latter be lower than 0.7 [17]. Other studies have also demonstrated that the presence of carboxyl groups enhanced the protein surface interaction [33], which had a straightforward impact on the biological outcome of the substrate [34].…”
Section: On the Acrylates Interaction With Rad16-imentioning
confidence: 99%